Patient compliance and supportive periodontal therapy: Study among young adults of Namakkal district - Subramanium Gokulanathan; Natarajan Balan; Ramaraj Jayabalan Aravind; Kavin Thangavelu (Wolters Kluwer Medknow Publications, 2014)
Aims: The aim of this study is to assess the patient compliance to supportive and maintenance periodontal therapy and to determine the reason for noncompliance among young adult patients of Namakkal district, India. Materials and Methods: This was a cross-sectional study conducted on 400 patients who underwent periodontal therapy and subsequently recalled for supportive and maintenance periodontal treatment in the Department of Periodontics, Vivekanandha Dental College for Women, Namakkal. Patients age group 25-35 years and of both gender were equally selected and grouped by occupation and socioeconomic status. According to their compliance with appointments, they are categorized as complete compliance, partially compliance and insufficient or noncompliance. Noncompliance and partially compliance patients were contacted and asked to rate their experience and reason for noncompliance. Results: In this study, 80% of patients showed complete compliance and were regular for supportive periodontal therapy appointments. Women were more regular in maintaining recall appointments than men. Salaried employers showed 84.3% complete compliance, while self-employed personals showed 77% complete compliance and 75% of nonworking personals were regular to the appointment schedule. Noncompliance person has quoted lack of time and forgetting the appointment date as a major reason for missed appointments. Conclusions: This study recommends the need for improvement in communication skills of practitioners and weekend appointment for patient undergoing periodontal maintenance therapy.